2020
DOI: 10.1159/000514533
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid-to-Albumin Ratio: A Novel Marker for the Extent of Coronary Artery Disease in Patients with Non-ST-Elevated Myocardial Infarction

Abstract: Objective: This research aimed to investigate the predictive value of the uric acid-to-serum albumin ratio (UAR) in establishing the severity and extent of coronary artery disease (CAD) with non-ST segment elevation myocardial infarction (NSTEMI) patients. Methods: A total of 402 patients (mean age 63.5 ± 11.6 years) were included in this retrospectively designed study. We compared Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery Scores (SS) between low (≤22) and intermediate-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 35 publications
3
40
0
2
Order By: Relevance
“…In a study evaluating UAR in non-STEMI patients and including 402 patients, the UAR value was associated with a high SYNTAX score and the prevalence of CAD. 13 In our study, the UAR was an important predictor of mortality in STEMI patients and increased UAR values were directly proportional to the risk of mortality when evaluated both continuously and categorically (Figures 2 and 3). The risk prediction of UAR for mortality risk in STEMI patients can be explained by the relationship of high UA with inflammatory process/oxidative risk and low SA with increased inflammation and catabolic process.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In a study evaluating UAR in non-STEMI patients and including 402 patients, the UAR value was associated with a high SYNTAX score and the prevalence of CAD. 13 In our study, the UAR was an important predictor of mortality in STEMI patients and increased UAR values were directly proportional to the risk of mortality when evaluated both continuously and categorically (Figures 2 and 3). The risk prediction of UAR for mortality risk in STEMI patients can be explained by the relationship of high UA with inflammatory process/oxidative risk and low SA with increased inflammation and catabolic process.…”
Section: Discussionsupporting
confidence: 50%
“…12 The uric acid/albumin ratio (UAR), which includes both of the mentioned parameters, may be related to the increased risk of mortality in patients with ACS, and also, a study showed that high UAR values were associated with an increased SYNTAX score. 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çakmak reported that UAR was an independent predictor of the severity of coronary artery disease but did not assess type A AAD speci cally [14]. In this study, we focused on patients diagnosed with type A AAD and treated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Heng Gao (  gaoheng19820109@163.com ) Shaanxi Provincial People's Hospital cerebrovascular disease and other cardiovascular diseases [11][12][13].Çakmak reported that the uric acid-toalbumin ratio (UAR) is a novel in ammatory marker that independently provides better predictive ability for outcomes than the C-reactive protein-to-albumin ratio; thus, UAR might be useful for predicting the extent of in on-ST-elevation myocardial infarction NSTEMI patients [14]. However, no studies have been conducted on the effect of UAR on the prognosis of patients with type A AAD, and whether the predictive value of UAR for prognosis differs from SA level or uric acid level.…”
mentioning
confidence: 99%